Meta-accuracy and relationship quality Weighing the costs and benefits of knowing what people really think about you. [article]. - Carlson, Erika N.
People use metaperceptions, or their beliefs about how other people perceive them, to initiate and maintain social bonds. Are accurate metaperceptions associated with higher quality relationships? In four studies, the current research answers this question but considers the possibility that the self might not experience the same relational benefits of accurate metaperceptions, or meta-accuracy, as the people who form judgments about the self. For example, people tend to like individuals who have accurate self-perceptions, yet individuals tend to enjoy their own relationships more with people they believe see them in desirable ways. To test whether meta-accuracy is linked to relationship quality and whether this link differs for the self and others, meta-accuracy for personality traits as well as metaperceiver- and judge-reported relationship quality were assessed among new acquaintances (N = 184), peers (N = 228), friends (N = 273), and romantic partners (N = 401). Results suggested that judges enjoyed relationships more with metaperceivers who knew the impression they made, regardless of whether judges' impressions were desirable (i.e., positive or self-verifying). Initial meta-accuracy also predicted greater relationship quality over time, suggesting that accurate metaperceptions have positive effects on relationships. In contrast, rather than enjoying relationships more when they were accurate, metaperceivers enjoyed relationships more when they believed judges perceived them in positive or self-verifying ways. Thus, meta-accuracy seems to be a virtue in the eyes of judges, but metaperceivers do not seem to reap the same benefits of knowing what others really think. Implications for improving meta-accuracy are discussed.- (from the authors)
Keywords: Metaperception; Self-knowledge.; Interpersonal perception; Personality; Relationships